Shared Decision-Making and the Yellow Fever Vaccine - Pastura, Patricia Cardoso (Ars Medica, 2020)
A girl born with central nervous system malformation is in the pediatric intensive care unit due to epilepsy. It is difficult to treat convulsions without sedating her. What can she feel? What can she hear? She is always asleep and her eyes remain closed. The parents are vulnerable, sad, desperate. In this story her life is told in a strange cadence of days until her first birthday, then the story concludes.